No longer taboo: liberalisation of sexual culture in Soviet Belarus during Khrushchev’s thaw - Huzhalouski, Alexander A. (Journal of the Belarusian State University. History, 2022)
The article presents the results of analysis of the main trends in the development of sexual culture in Belarusian society during the Khrushchev thaw. Based on the study of archival materials and periodicals of the years under investigation, a characteristic of the Soviet Belarus population sexual behaviour, mainly young people, is given. The latter was characterised by profound changes: decrease in the age of sexual debut, change in the nature of family and marriage relations, weakening of moral prohibitions, erosion of gender stereotypes, etc. These changes were accelerated by the opening of the «iron curtain», through which slipped the ideas and practices of the sexual revolution which first swept the United States and then Europe. The thaw was accompanied by an explosion of public interest in books, films, theatrical performances dedicated to love, the problems of relationships between men and women. Along with personal emancipation, the liberalisation of sexual culture brought negative trends in the form of an increase in the number of divorces and abortions, the number of unwanted pregnancies and morbidity. The departure from the Stalinist family and marriage model, strict regulation of the reproductive behaviour of the population in particular, reflected in a number of new legal acts accumulated in the Code on Marriage and Family of the Belarusian SSR adopted by the Supreme Council of the BSSR 1969 June 13.